PREPARO, CARACTERIZAÇÃO E AVALIAÇÃO DA TOXICIDADE E DO POSSÍVEL EFEITO TERMOGÊNICO DE NANOEMULSÕES CONTENDO ÓLEO ESSENCIAL DE CANELA (Cinnamomum cássia) - Fortes, Carolina Rapachi (2019)
Obesity is considered a worldwide public health problem, being characterized by excessive accumulation of body fat and associated with the appearance of other pathologies. Alternatives for the control of obesity are being proposed, such as the use of essential oils with thermogenic power, such as cinnamon essential oil, because they promote the maintenance of body weight when associated with a calorie-restricted diet. Cinnamon oil has a low water solubility and low oral bioavailability. Nanotechnology emerges as an alternative so that we can meet the growing demand of the consumer allied to the advancement of technology to seek new forms of presentation of products that help in the treatment of overweight / obesity. In this context, a nanoemulsion was produced using cinnamon oil (NO) as active and white nanoemulsion (NB), that is, without the study active, for comparison purposes. Both nanoemulsions had their physical-chemical parameters, such as zeta potential, mean particle diameter, polydispersion index, pH and stability evaluated for 90 days to verify under which conditions the mentioned nanoemulsions remained stable, enabling to determine the best storage condition. After these studies, NO and NB were analyzed in relation to the following activities: cytotoxicity and genotoxicity by PicoGreen®, Nitric Oxide and Production Rate of Reactive Oxygen Species, antioxidant activity by ABTS method, toxicity and possible thermogenic effect in Wistar rats. The results obtained revealed that NO and NB remained stable under refrigeration (5 ºC), did not present in vitro cytotoxicity and presented a potential antioxidant activity. The in vivo study showed that animals treated with free cinnamon essential oil (OC) and NO showed no toxicity through the parameters analysed during eight weeks of treatment. There was a possible thermogenic effect, as there was a significant decrease in body mass of animals treated with cinnamon essential oil and NO. This way, we can conclude that nanotechnology emerges as a possibility to improve the efficiency, stability and oxidation of the essential oil of cinnamon with the production of a nanoemulsion and also to be a viable alternative, using natural assets for weight maintenance.